Saberes e fazeres do supervisor de ensino de uma diretoria da Rede Estadual Paulista, em relação ao trio gestor - Andrade, Maria de Fátima Colaço Correia de (2012)
This paper is part of the line of research Educator Training of the Post-Graduation Program: Curriculum of the Pontifical Catholic University of São Paulo. The objective of this work is to investigate knowledge and actions of the Educational Supervisor of the public school network of São Paulo, as part of the management trio of public schools, together with the Principal and the Teacher Coordinator, proposing a critical reflection on the supervising function, in order that paths are uncovered and educational supervision is reframed, regarding school teaching-learning process and democratic management. The methodology was based on a qualitative approach, bibliography research, document analysis and field research. The setting of the research was a Director of Education in São Paulo and the subject researched were five Educational Supervisors, five school Principals and five Teachers Coordinators. During this research about knowledge and actions of Education Supervisors, we noticed that Supervisors, as members of the managing team of public schools of the state of São Paulo, are experiencing a changing process in their field of work, thus requiring specific knowledge. The supervising and controlling character of the supervising action in the past is giving way to a necessary mediating and articulating profile of the education supervision in schools. However, the role of supervision, as a member of the management trio of public schools, is still fragile due to the complexity of actions, excessive administrative tasks and central agencies demands. The subjects studied showed that educational supervision should be more focused on pedagogical aspects, therefore, we believe that the supervising function should be subject of discussion, training and investigation of education systems, so that paths can be tracked and this professional can better collaborate with the teaching-learning process and the school democratic management, taking into consideration the needs of the contemporary school